Lecithin-enriched diet improves growth performance, lipid metabolism and disease resistance in giant river prawn (Macrobrachium rosenbergii) - Qiu, Zongsheng; Xu, Qiyou; Chong, Chou Min; de Cruz, Clement R. (Elsevier, 2026)
Lecithin is widely used in aquafeeds for its roles in lipid absorption and immunity, but comparative studies on different sources remain limited, especially in crustaceans. In this study, a 56-day feeding trial was conducted to comprehensively examine the effects of various lecithin sources including soybean (SL), sunflower (SFL), egg yolk (EYL), and lysolecithin (LL) on the growth performance, biochemical indicators, and disease resistance of Macrobrachium rosenbergii. The results revealed that lecithin supplementation significantly improved weight gain, feed conversion ratio, and lipid metabolism, and with LL exhibiting the most notable effects. Antioxidant capacity was enhanced, as indicated by improved superoxide dismutase (SOD) and catalase (CAT) activities and decreased malondialdehyde (MDA) levels, particularly in the EYL and LL dietary treatments. Histological analysis of the hepatopancreas revealed decreased lipid droplet deposition and improved cellular integrity. Furthermore, the bacterial challenge test with Aeromonas hydrophila established that lecithin supplementation significantly improved disease resistance, with the lowest mortality rate in the LL dietary treatment. The study demonstrates that dietary supplementation with lecithin derivatives, particularly LL, significantly improves growth parameters, lipid metabolism, antioxidant status, and disease resistance in Macrobrachium rosenbergii.